Perceived usability: How computer interaction design is informing production design - Trevor, Martin (Biennale of Electronic Arts, 2007)
Computing is providing a great deal of information in regards to interaction design and in particular the connection between emotion and perceived usability. In 1995, Masaaki Kurosu and Kaori Kashimura gave a short paper at the Conference on Human Factors in Computing Systems, documenting research that strongly indicated the positive effects of aesthetics on apparent usability, after studying different layout controls for ATMs. These findings were repeated, and with more profound results by a doubting Israeli scientist Noam Tractinsky (1997) who felt that the original research may have suffered from a cultural bias. Designer and psychologist Donald Norman in 2004 devoted a chapter, entitled ‘Attractive Things Work Better’ in his book ‘Emotional Design: Why we love or hate everyday things’ (2004) where he contends that positive emotions aid in the decision making process that are critical to learning, curiosity and creative thought. This paper will provide a critical review of human factors research and practice into computer interaction design. In particular it will focus on the user’s emotional state and perceived usability and how it can inform product design. The links between: pleasure and happiness; aesthetics (style, beauty, attractiveness); self confidence in the user and usability will be discussed.